Chemoselective silicification of synthetic peptides and polyamines - Abacilar, Maryna; Daus, Fabian; Geyer, Armin (Beilstein Journal of Nanotechnology, 2015)
Biosilicification sets the standard for the localized in vitro precipitation of silica at low orthosilicate concentrations in aqueous environment under ambient conditions. Numerous parameters must be controlled for the development of new technologies in designing inventive nanosilica structures, which are able to challenge the biological templates. A long neglected requirement that came into focus in the recent years are the cellular techniques of preventing unintentional lithification of cellular structures since numerous cellular components such as membranes, DNA, and proteins are known to precipitate nanosilica. The diatom metabolism makes use of techniques that restrict silicification to an armor of silica around the cell wall while avoiding the petrifying gaze of Medusa, which turns the whole cell into stone. Step by step, biochemistry unveils the hierarchical interplay of an arsenal of low-molecular weight molecules, proteins, and the cytoskeletal architecture and it becomes clearer why the organisms invest much metabolic effort for an obviously simple chemical reaction like the precipitation of amorphous silica. The discrimination between different soluble components in the silicification process (chemoselective silicification) is not only vitally important for the diatom but poses an interesting challenge for in vitro experiments. Until now, silica precipitation studies were mainly focused on the amount, the morphology, and composition of the precipitate while disregarding a quantitative analysis of the remaining soluble components. Here, we turn the tables and quantify the soluble components by 1H NMR in the progress of precipitation and present experiments which quantify the additivity, and potential cooperativity of long chain polyamines (LCPAs) and cationic peptides in the silicification process.
Keywords: biomineralisation; biosilicification; NMR spectroscopy; polyamines; silaffin